Estratégias competitivas utilizadas pelas empresas atacadistas de alimentos e bebidas do estado do PIAUÍ - Barbosa Sobrinho, Diógenes Eldo Carvalho de (2010)
The wholesale sector represents a meaningful segment for the State of Piauí, in terms of tax revenue for the State and in the generation of direct jobs. Due, however, the change of channels of distribution, which industries search for commercial partners more specialized to focus on the distribution of their products, the traditional wholesale feels these pressures which are: the gradative substitution of its services for companies more specialized in the channel of distribution, the formation of buying centers by retailers who negotiate directly from the industry, eliminating the traditional wholesale. This way, the traditional wholesalers need to make use of strategies that help these organizations to stand on this market. The general objective of this study is to analyze the competitive strategies adopted by unionized companies of the wholesale sector of food and drink in the State of Piauí, in order to compete in the market. In the theoretical referential were approached: the model of five competitive forces of Porter and the competitive strategies influenced by these competitive forces. In the methodological aspects it is a work of descriptive nature, bibliographical and documental. It was made a field research by means of a questionnaire applied in the unionized wholesale companies in Piauí. The results showed that the traditional type of wholesale predominate in the researched segment. There is not a standard behavior in relation to the competitive strategies of the wholesale companies of food and drink in the State of Piauí. It was observed in the sample that two companies make use of low cost strategies, two companies make use of differentiation strategy and two companies make use of focalization strategy.